Study to assess psychological distress among undergraduate Medical and Engineering students of Delhi - Imaan, Fatima; Rasania, Sanjeev Kumar; Imaan, Zainab; Kushwaha, Sonam (Indian Journal of Community Health, 2025)
Background: Undergraduate students, especially those in medical and engineering fields, face significant academic pressures coupled with other stressors which makes them susceptible to mental distress, including anxiety, depression, and sleep disturbances. Objective: To assess and compare mental distress among undergraduate medical and engineering students and factors affecting it. Materials and Methods: A comparative cross-sectional study was conducted among 300 students (150 each from medical and engineering colleges of Delhi, India. Data was collected using a structured online questionnaire, which included demographic details and the Kessler Psychological Distress Scale (K10) to assess mental distress. Results: We observed that 61.3% of participants were likely to have some sort of stress disorder, with higher prevalence in medical students (62.7%) than in engineering students (60%). Longer sleep latency was significantly associated with moderate to severe stress disorders (p < 0.001). Association of gender with mental distress was also found to be significant (p value= 0.022). Conclusions: Medical students were more prone to severe stress disorders compared to engineering students. Prolonged sleep latency was a strong predictor of psychological distress. Early intervention and mental health support are essential for improving student well-being.